DAMPAK KOMUNIKASI GENERASI MILENIAL TERHADAP PERILAKU NOMADIC TOURISM - Parwoto, Boby Dimas; Harjanto, Adella Gloria; Peja, Elmira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
The purpose of this research is to analyze the impact of the application of the concept of nomadic tourism to travel patterns and use descriptive methods with quantitative and qualitative approaches through social media-based surveys on tourist attractions in the Orchid Forest Cikole, Bandung. The pattern of traveling in this 4.0 era, for the most respondents mixed of generations Y and Z, are able to travel twice a year and prefer to travel in low sessions (71.3%). In financial planning, they do not need to save money, because with minimal funds they can take a vacation on an impromptu basis, seeing the review as their main consideration for a vacation. However, the presence of virtual reality or augmental reality facilities will have a negative impact on income for nomadic destinations / attractions. The concept of nomadic tourism, applied in the Orchid Forest Cikole attraction, Bandung has not been very effective, because most tourists who come feel more secure and comfortable using the concept of non-nomadic tourism. And in terms of digital tourism, these attractions can already be accessed through google maps and have been instagramable, as well as reviews of these attractions can already be accessed via Social Media or YouTube. Keywords: Nomadic Tourism, Industrial Revolution 4.0, Impact and Transformation